Enhancing Poetry Teaching Practices in the EFL Classrooms: An Exploratory Action Research - Bhatt, Deepak (Exploration अन्वेषण, 2026)
Teaching poetry is an influential tool for developing language proficiency and emotional excellence among learners of English as a Foreign Language (EFL) in Nepal. However, poetry teaching plays a crucial role in language learning in EFL classrooms; it remains teacher-centred, resulting in low student participation. This exploratory action research (EAR) was designed and carried out to find out why secondary-level students remain inactive during poem teaching and how the interaction between the teacher and students can increase participation of the students. The study was carried out in a Grade 10 English classroom with 32 students aged 15 to 16, over a period of six weeks. The researcher used the questionnaires as a tool to collect data. The study found that students were passive in the poetry classroom because of language difficulties, unfamiliar cultural content, and teacher-centred teaching strategies. To solve this, two action cycles were used with activities like predicting before reading, explaining the context and figures of speech used in the poem, reading in pairs with rhyme and rhythm, and allowing students to make critical interpretations and write summaries on their own. As a result of this intervention, students became more confident and motivated, developed a better understanding of poems, and showed increased participation in classroom activities. The study shows that using learner-centred and reflective strategies can make poetry lessons more active, interesting, and engaging for students. It also shows that exploratory action research helps teachers improve their teaching skills, especially in an EFL setting.